2011
DOI: 10.1002/pat.1751
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of a hyperbranched charring and foaming agent on flame retardancy of polyamide 6

Abstract: A hyperbranched polyamine was prepared using an A2 + B3 approach. It acted as a hyperbranched charring and foaming agent (HCFA) in combination with ammonium polyphosphate (APP) to form a new intumescent flame retardant (IFR) system for polyamide 6 (PA6). Effect of HCFA on flame retardant and thermal degradation properties of IFR‐PA6 was investigated by limiting oxygen index (LOI), UL‐94 vertical burning, cone calorimeter, and thermogravimetric analysis (TGA) tests. The IFR system presented the most effective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The initial decomposition temperature (T 5 ), the temperature of the maximum mass loss rate (T max ), estimated on the basis of the DTG maximum peak, and the char yield at 700˝C (W I ) measured in both environments are listed in Table 1. The thermal decomposition behavior of neat PA6 and PA6 formulations with different FR systems based on non-meltable melamine derivatives has been well studied [7,[37][38][39][40]. In the nitrogen environment (Figure 2), PA6 has a T 5 value of approximately 388˝C, decomposed in one stage process with T max of about 455˝C, leaving negligible char at 700˝C (0.28 wt %), which can be attributed to the partial decomposition of the cross-linked structure at the final stage of the decomposition process.…”
Section: Thermal Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The initial decomposition temperature (T 5 ), the temperature of the maximum mass loss rate (T max ), estimated on the basis of the DTG maximum peak, and the char yield at 700˝C (W I ) measured in both environments are listed in Table 1. The thermal decomposition behavior of neat PA6 and PA6 formulations with different FR systems based on non-meltable melamine derivatives has been well studied [7,[37][38][39][40]. In the nitrogen environment (Figure 2), PA6 has a T 5 value of approximately 388˝C, decomposed in one stage process with T max of about 455˝C, leaving negligible char at 700˝C (0.28 wt %), which can be attributed to the partial decomposition of the cross-linked structure at the final stage of the decomposition process.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…In fact, the thermal decomposition of Exolit OP 1230 in the PA6 formulation might be the result of the degradation of the additive and its vaporization, which might constitute the dominant process [41]. Former studies on PA6 formulations containing melamine or melamine derivatives also reveal an increased destabilization of the PA6 polymer caused by the incorporation of FR additives [8,38,39]. Considering the small reduction of T 5 in the PA6/DTE-DOPO formulation as compared to neat PA6, it seems that the thermal decomposition process of this formulation may be initiated with the release of the FR additive.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…Ke et al synthesized a hyperbranched charring and foaming agent (HCFA), which has a continuous reaction process, short reaction time, good thermal stability, and high char yield. However, the behavior of the water resistant ability have not been investigated [28,30].…”
Section: A N U S C R I P Tmentioning
confidence: 97%
“…In recent years, hyperbranched polymers have received considerable attention in IFR [24][25][26][27][28][29][30][31]. It was found that triazines and their derivatives are good charring agents because of their abundant nitrogen, tertiary nitrogen structure and its integration of carbon sources and foaming agents.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…A hb polyamine (hb-PAm) was prepared by Ke et al [269] utilizing the A 2 + B 3 approach where s-triazine was the B 3 monomer and ODA was the A 2 monomer. The representative hb-PAm structure is shown Scheme 31.…”
Section: Hyperbranched Poly(aryl Amine) As Flame Retardant For Pa6mentioning
confidence: 99%